Protection of Intellectual Property Rights for University Students in License Agreements in Indonesia: Encouraging Technological Innovation through Research and Learning Outcomes in Higher Education - Budi Suharto; Ucu Cahyana; Bedjo Sudjanto (EduTech Journal, 2025)
This study aims to explore the level of students ' understanding of Intellectual Property Rights( IPR), the implementation of IPR protection policies in universities, as well as their impact on technological innovation and learning outcomes. Using a qualitative approach, data was collected through in-depth interviews with students, lecturers, and university managers. The results showed that students ' understanding of IPR, particularly related to licensing agreements, was still limited, although involvement in research projects increased their awareness. Universities already have IPR protection policies, but their implementation still faces obstacles such as complicated regulations, limited resources, and lack of administrative support. IPR protection is proven to encourage students to innovate, increase motivation, and research competence and their legal literacy. The study recommends improving IPR literacy through formal education, the establishment of IPR-specific units at universities, and collaboration between universities, governments, and industry sectors to support the protection of Student Innovation.